Clear cell type of renal cell carcinoma with numerous hyaline globules: a diagnostic pitfall - Hes, Ondrej; Benakova, Katarina; Vanecek, Tomas; Sima, Radek; Michal, Michal (Pathology international, 2005)
A unique and never-before-published example of clear cell renal cell carcinoma (CRCC) found among 9000 primary renal cell tumors is presented. The tumor contained such a dense concentration of glassy hyaline globules (GHG) in the cytoplasm of the neoplastic cells that it overshadowed the morphology of the neoplasm. The resulting appearance of the tumor was quite misleading and different from the conventional CRCC. The GHG were 7-30 microm in diameter. They were glassy and pale to slightly eosinophilic in color in hematoxylin-eosin. The GHG stained positively with periodic acid-Schiff and negatively with silver and Hale's colloidal iron. Immunohistochemically, they were also negative for anti Mycobacterium bovis antigen. At the ultrastructural level, the GHG were formed by an amorphous mass of stellate shape. The GHG were localized within rough endoplasmic reticulum. Molecular genetically, mutation of the distal part of exon 3 of the VHL gene causing elongation of the VHL protein was found in the tumor, thus confirming the diagnosis of CRCC.
Keywords: nádory ledvin; Kidney Neoplasms; sekvenční analýza RNA; ubikvitinligasy; Humans; sekvence nukleotidů; DNA primery; messenger RNA; lidé středního věku; Frameshift Mutation; Von Hippel-Lindau Tumor Suppressor Protein; Molecular Sequence Data; nádorové supresorové proteiny; molekulární sekvence - údaje; spironolakton; hyalin; výsledek terapie; lidé; Tumor Suppressor Proteins; Ubiquitin-Protein Ligases; posunová mutace; Amino Acid Sequence; RNA, Neoplasm; RNA, Messenger; RNA nádorová; Base Sequence; Male; Middle Aged; Cytoplasm; Treatment Outcome; DNA Primers; Spironolactone; karcinom z renálních buněk; Hyalin; cytoplazma; Carcinoma, Renal Cell; Nephrectomy; DNA nádorová; mužské pohlaví; nefrektomie; nádorový supresorový protein VHL; Sequence Analysis, RNA; DNA, Neoplasm; sekvence aminokyselin